PRINCIPLES OF SECONDARY EDUCATION SYSTEM MANAGEMENT - Mamatov, Jasur; Ganiyev, E (Журнал математики и информатики, 2021)
If we focus on the reconstruction of the secondary education system from the moment of independence of our country, it is important to analyze the regional secondary education system, to take into account the interaction in solving its problems.